Pemanfaatan Fitur Trending Topic Twitter “X” sebagai Upaya Pemenuhan Kebutuhan Informasi Mahasiswa Program Studi Perpustakaan dan Ilmu Informasi Universitas Negeri Padang - Qalbina, Gita Syifa; Asmara, Rini (Al-DYAS, 2024)
This research is motivated by the phenomenon of widespread misuse of information spread on social media. Therefore, this study aims to describe how the utilization of Twitter's "X" trending topic feature fulfills the information needs among students of the Library and Information Science major at Universitas Negeri Padang. This research uses a quantitative method with a descriptive approach. The research sample consists of 80 students from the Library and Information Science major, with data obtained through the distribution of questionnaires to respondents according to the research criteria. Based on the data, the study found that the utilization of Twitter's "X" trending topic feature among students of the Library and Information Science major at Universitas Negeri Padang is categorized as good, falling within the interval scale of 3.41 – 4.20. Additionally, the fulfillment of information needs among students of the Library and Information Science major through the utilization of Twitter's "X" trending topic feature is also categorized as good, within the same interval scale of 3.41 – 4.20. Thus, it can be concluded that through the utilization of Twitter's "X" trending topic feature, the information needs of students can be fulfilled.